Kidney-protective Effect of Magnesium Supplementation in Cisplatin-containing Chemotherapy for Pediatric Cancer: A Retrospective Study. Issue 5 (July 2018) - Matsui, Motohiro; Saito, Yuya; Yamaoka, Shoko; Yokokawa, Yuichi; Morikawa, Yoshihiko; Makimoto, Atsushi; Yuza, Yuki
Abstract : In total, 158 chemotherapy courses containing cisplatin for 37 pediatric cases of newly diagnosed cancer were divided into 2 groups depending on whether magnesium (Mg) supplementation was administered (Mg+: 92 courses) or not (Mg−: 66 courses). Renal impairment was defined as grade 2 or higher creatinine elevation (CE) after each chemotherapy course. The incidence of CE in the Mg+ was significantly lower than in the Mg− (9.8% vs. 22.7%; P =0.025). Multivariate analysis revealed that Mg supplementation significantly reduced the incidence of CE (odds ratio, 0.36; confidence interval, 0.13-0.99). In pediatric patients, Mg supplementation during cisplatin-containing chemotherapy was associated with less cisplatin-induced nephrotoxicity to prevent cisplatin-induced nephrotoxicity.